Exchange Rate Reform and Structural Disturbances in a Dual Exchange Rate Economy. (IMF Working Papers; Working Paper ;, 1988)
This paper analyzes the implications of devaluation and a variety of structural disturbances in a dual exchange rate economy. A key feature of the model developed is its explicit recognition of both private (fraudulent) and officially-sanctioned cross transactions between the two exchange markets. The principal lesson to be learned from the analysis is that popular notions as to the effects of devaluation or of other disturbances are to be viewed with considerable caution when the dual rate regime involves inter-market transactions.